Principles for evaluating health risks in children associated with exposure to chemicals. - Who (World Health Organization, 2006)
This new volume in the Environmental Health Criteria (EHC) Series provides a systematic analysis of the scientific principles to be considered in assessing health risks in children; taking into account their unique susceptibilities. The terms children and child as used in this report include the stages of development from conception through adolescence. This new EHC builds on previous volumes addressing methodologies for assessing risks in children: EHC 30, Principles for Evaluating Health Risks to Progeny Associated with Exposure to Chemicals During Pregnancy (WHO, 1984) and EHC 59, Principle.